18-12x-3=10x+15-2x

Simple and best practice solution for 18-12x-3=10x+15-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18-12x-3=10x+15-2x equation:


Simplifying
18 + -12x + -3 = 10x + 15 + -2x

Reorder the terms:
18 + -3 + -12x = 10x + 15 + -2x

Combine like terms: 18 + -3 = 15
15 + -12x = 10x + 15 + -2x

Reorder the terms:
15 + -12x = 15 + 10x + -2x

Combine like terms: 10x + -2x = 8x
15 + -12x = 15 + 8x

Add '-15' to each side of the equation.
15 + -15 + -12x = 15 + -15 + 8x

Combine like terms: 15 + -15 = 0
0 + -12x = 15 + -15 + 8x
-12x = 15 + -15 + 8x

Combine like terms: 15 + -15 = 0
-12x = 0 + 8x
-12x = 8x

Solving
-12x = 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-12x + -8x = 8x + -8x

Combine like terms: -12x + -8x = -20x
-20x = 8x + -8x

Combine like terms: 8x + -8x = 0
-20x = 0

Divide each side by '-20'.
x = 0.0

Simplifying
x = 0.0

See similar equations:

| -19=-7+2y | | x-6.1=-0.2 | | 25=8x+9 | | 24=h+19 | | 7(5x-4)=14 | | x-3.7=2.1 | | x-2=2x+11 | | 44=.5(x+3)x | | 14=y-13 | | x+3.8=6.1 | | 4x-8=-28 | | 2x+11=x-2 | | 5(u-4)-1=-4(-4u+9)-5u | | 14+3a=3-4(5a+3) | | 7=3x+4 | | 64x^2+80x+25= | | 6x-2x+8+9y-8y-2= | | 450000-22000x=0 | | 3x-2=3x-3 | | 7.27n+6.2=5.2n+12.41 | | 8c-4d=0 | | 2=21 | | log(x+8)-log(x)=1 | | 2c=25 | | 9x-72=x | | 128/32=x | | 4x+6=6x+4 | | 3x+7x=0 | | 3x^2+28x+60=0 | | 450000-22000x=155000+12000x | | 3y^4-2y^2-7=0 | | -5x+7=22 |

Equations solver categories